Periorbital Necrotising Fasciitis after Minor Skin Trauma - Ceren Günel; Aylin Eryılmaz; Yeşim Başal; Ali Toka (Case Reports in Otolaryngology)
Necrotizing fasciitis (NF) is a fatal and rare disease, mainly located in extremity and body. Due to the good blood supply, the occurrence of this infective disease of skin and subcutaneous tissue/fascia is much rarer in the head and neck region. In this study, we represent periorbital necrotizing fasciitis case in a patient with normal immune system. The patient applied the emergency clinic with the complaints of swelling and redness on the left eye. It was found out that a skin incision occurred at 2 cm below the left eye with razor blade 2 days ago. After taking swab culture sample, patient was started on parenteral Vancomycin + Ampicillin-Sulbactam treatment. It was observed that necrosis spread within hours and an emergent deep surgical debridement was performed. Following the debridement, it was observed that periorbital edema began to regress prominently on the 1st day of the treatment. Treatment was carried on with daily wound care and parenteral antibiotherapy. The patient was discharged from the hospital with slightly cosmetic defect.